Chelating-Agent-Enhanced Copper, Lead and Zinc Extraction From Iraqi Contaminated Sandy Soil. - Asal Gzar, Hatem; Mohsin Kseer, Khamaal (International Journal of Engineering and Technology, 2018)
This research aims to investigate extraction of copper, lead, and zinc from Iraqi sandy contaminated soil. Two systems were tested single and ternary component systems. Chelating agent ethylenediaminetetraacetic acid disodium salt (Na2EDTA) was utilized as extractant. Amount of 500 mg of metal per kg soil was prepared to form artificially contaminated soil. Extraction of metals was achieved using column extraction mode. Experimental tests were conducted at different conditions of Na2EDTA concentration,flow rate, and contact time. The results illustrated that the maximum removal percentages for single component system were 92% ,76% and 68% at equilibrium time 6, 8, and 8 hours for Pb , Cu and Zn, respectively. While for ternary system were 82%, 72% and 65%, respectively, at equilibrium time 6 hours for Cu and 8 hours for Pb and Zn. In addition to the best equilibrium time, the other optimum conditions for both systems were 0.1 mol/L extractant concentration, pH 4 and flow rate 20 ml/hr. The sequence of heavy metals removal was Pb > Cu >Zn. The experimental data were tested by applying it in four kinetic models; first order, two constant, parabolic diffusion, and Elovich model. Elovich and parabolic diffusion were the most fitted models to the experimental data.